PROGRAM PENYULUSAN MAKANAN SEHAT DAN PENGGUNAANGARAM BERYODIUM - Sumedi P Nugraha (UII, 2013)
Lack of knowledge of citizens about the food they consume daily, as well as mostpeople are still using less salt isnot iodized feasible and less good for health makes theauthor moved to the extension of the benefits of the food consumed daily as well as thebenefits of iodized salt.The program is carried out as much as six timesandthe face toface for 2 hours. This extension materials are as follows: 4 healthy 5 perfect food, thebenefits of eating agricultural produce Hamlet Cangkol Duwur terms of health, thebenefits of iodized salt, as well as the testing of samples of salt with iodine-test to provethat iodizedsalt or not.The result of this program goes well and fluently. In addition,people are also very happy and excited in receiving the material. author sincerely hopethrough this program, citizens have the knowledge of the benefits of the food theyconsumeeveryday and consume iodized salt.